Covid-19, nutrition and pseudoscientific claims - Abdolreza Norouzy (World Nutrition Journal, 2022)
The COVID‐19 infodemic is full of false claims, half backed conspiracy theories and pseudoscientific therapies, regarding the diagnosis, treatment, prevention, origin and spread of the virus. Correcting misrepresentations should be viewed as a professional responsibility